2016
DOI: 10.1039/c5ce02264a
|View full text |Cite
|
Sign up to set email alerts
|

Strong luminescent copper(i) halide coordination polymers and dinuclear complexes with thioacetamide and N,N′-donor ligands

Abstract: Ternary compounds based on copper(i) halides with thioacetamide and 4,4′-bipyridine or pyrazine have been prepared and characterized showing luminescence and semiconductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 66 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…This observation has also been verified for CPs where (CuI)x clusters are part of the structural moiety of the compound, with the same findings [9,72]. In some cases, the thermochromic behavior of these clusters can be combined with the properties of another feature of the compound, like another metal structure.…”
Section: Temperature-dependent Propertiessupporting
confidence: 64%
“…This observation has also been verified for CPs where (CuI)x clusters are part of the structural moiety of the compound, with the same findings [9,72]. In some cases, the thermochromic behavior of these clusters can be combined with the properties of another feature of the compound, like another metal structure.…”
Section: Temperature-dependent Propertiessupporting
confidence: 64%
“…[6a, 89] Therefore, the structures of compounds 1-3 showing sulphur atoms bridging metal centres are materials of potential interest in terms of electrical behaviour. Therefore, several single-crystals of these compounds has been measured using a two-probe method at 300 K (Figures S12-14).…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the fact that the metal orbital energies are better matched for sulfur, leading to a higher delocalization of the spin/charge density through the bridging atoms. Despite the fact that there are some examples of Cu(I) halide coordination polymers based on organosulfur ligands with luminescent properties,[6] those that show stimuli-responsive luminescent are less frequent, and are usually based in cubane-like Cu 4 I 4 or rhombohedral Cu 2 I 2 clusters. [7] In this work, we have studied the preparation and characterization of a series of coordination polymers based on the combination of copper(I) halides with 4-mercaptophenol.…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers (CPs) are a large group of compounds which depending on the selected building blocks (metal ions and organic ligands) have a great structural variety and an immense diversity of physical and chemical properties. Thanks to their infinite structure and function tailorability that originates from the abundant building blocks, these materials can present, among other properties, interesting electrical conductivity. For instance, the paradigmatic case of MMX chains with platinum, iodine, and dithiocarboxylato ligands is particularly outstanding due to its high electrical conductivity even at room temperature, as well as the metallic to semiconducting phase transitions showed by them with the temperature. , Their intriguing features have also been analyzed at the nanoscale to demonstrate their potential as a source of novel molecular wires. , Indeed, several CPs show significant electrical conductivity. In this context, copper­(I) halides have been subjected to a number of studies, particularly for those with ligands with π* or σ* orbitals suitable for efficient d π metal orbitals overlapping. ,, As a result of their structural diversity, originating from the polymerization of copper–halogen-based subunits, double Cu–X chains are a subclass of CPs that can generate multifunctional materials showing combination of electrical conductivity and photoluminescence. ,, Moreover, the electrical conductivity found in some of the Cu–X double chains suggests their potential use as electronic materials . The features reported on copper­(I) double chains with iodide as bridging ligands are also noticeable, since they show interesting luminescent properties. ,,,, More recently, we have found that although this family of compounds shows rather similar structures the double Cu–I chain presents a high degree of structural flexibility, suggesting an elastic spring like behavior when these CPs are exposed to external physical and/or chemical stimuli.…”
Section: Introductionmentioning
confidence: 99%